Adaptive Interval Type-2 Fuzzy Logic Control for PMSM Drives With a Modified Reference Frame - Chaoui, Hicham; Khayamy, Mehdy; Aljarboua, Abdullah Abdulaziz (IEEE transactions on industrial electronics (1982), 2017)
In this paper, an adaptive interval type-2 fuzzy logic control scheme is proposed for high-performance permanent magnet synchronous machine drives. This strategy combines the power of type-2 fuzzy logic systems with the adaptive control theory to achieve accurate tracking and robustness to higher uncertainties. Unlike other controllers, the proposed strategy does not require electrical transducers and hence, no explicit currents loop regulation is needed, which yields a simplified control scheme. But, this limits the machine's operation range since it results in a higher energy consumption. Therefore, a modified reference frame is also proposed in this paper to decrease the machine's consumption. To better assess the performance of the new reference frame, comparison against its original counterpart is carried-out under the same conditions. Moreover, the stability of the closed-loop control scheme is guaranteed by a Lyapunov theorem. Simulation and experimental results for numerous situations highlight the effectiveness of the proposed controller in standstill, transient, and steady-state conditions.